Diagnosis of carotid sinus hypersensitivity in older adults: carotid sinus massage in the upright position is essential. Issue 1 (1st January 2000) - Parry, S W; Richardson, D A; O'Shea, D; Sen, B; Kenny, R A
Abstract : OBJECTIVE: To assess the diagnostic value of supine and upright carotid sinus massage in elderly patients. DESIGN: Prospective controlled cohort study. SETTING: Three inner city accident and emergency departments and a dedicated syncope facility. PATIENTS: 1375 consecutive patients aged > 55 years presenting with unexplained syncope and drop attacks; 25 healthy controls. INTERVENTIONS: Bilateral supine carotid sinus massage, repeated in the 70° head up tilt position if the initial supine test was not diagnostic of cardioinhibitory and mixed carotid sinus hypersensitivity. MAIN OUTCOME MEASURES: Diagnosis of cardioinhibitory or mixed carotid sinus hypersensitivity; clinical characteristics of supine v upright positive groups. RESULTS: 226 patients were excluded for contraindications to carotid sinus massage. Of 1149 patients undergoing massage, 223 (19%) had cardioinhibitory or mixed carotid sinus hypersensitivity; 70 (31%) of these had a positive response to massage with head up tilt following negative supine massage (95% confidence interval, 25.3% to 37.5%). None of the healthy controls showed carotid sinus hypersensitivity on erect or supine massage. The initially positive supine test had 74% specificity and 100% sensitivity; these were both 100% for the upright positive test. The clinical characteristics of the supine v upright positive subgroups were similar. CONCLUSIONS: The diagnosis of carotid sinus hypersensitivity amenable to treatment by pacing may be missed in one third of cases if only supine massage is performed. Massage should be done routinely in the head up tilt position if the initial supine test is negative.